A sensitivity analysis of numerical predictions for beryllium erosion and migration in ITER. (March 2021) - Romazanov, J.; Brezinsek, S.; Pitts, R.A.; Kirschner, A.; Eksaeva, A.; Borodin, D.; Veshchev, E.; Neverov, V.S.; Kukushkin, A.B.; Alekseev, A.G.; Linsmeier, Ch.
Abstract: The present study addresses the uncertainties that affect the recently performed predictions of beryllium (Be) erosion and migration in ITER using the Monte-Carlo code ERO2.0. The focus of the study is a D–T baseline discharge with fusion power gain Q = 10, scrape-off layer (SOL) input power P SOL = 100 MW, toroidal plasma current I p = 15 MA, and central toroidal field B t = 5.3 T . The parameter studies used to investigate uncertainties include variations of the radial extrapolation of plasma parameters in the far-SOL (scan A), the assumptions on impact angle distributions (scan B) and the anomalous transport of eroded Be (scan C). Variations by factors ∼ 3, ∼ 18 and ∼ 2 for scans A, B and C, respectively, are found. Highlights: ERO2.0 code predicts erosion of ITER beryllium First Wall in D–T baseline discharges. Parameter studies were performed to investigate the uncertainties of the predictions. Extrapolation of plasma profiles to the First Wall leads to variation by factor 3. Variation of D + and D 0 impact angle leads to variation by factor 18. Variations of Be diffusion coefficient leads to variation by factor 2.